Leber’s Hereditary Optic Neuropathy with Neurological Abnormalities. Case Report - N. A. Andreeva; N. L. Sheremet (Oftalʹmologiâ)
Leber’s hereditary optic neuropathy (LHON) is a maternal inherited mitochondrial disease characterized by bilateral vision loss in working age population. Although this pathology affects the retinal ganglion cells, the main manifestation of the disease is visual loss, the disease in some cases can occur as LHON+ with additional neurological and cardiological symptoms. This article presents a clinical case of a 42-year-old female patient with central vision loss and neurological symptoms. In addition to visual impairments, the patient notes numbness of the feet and shins, which have progressed over time, periodic tremor of the hands, weakness in the legs. Since 2013, the patient has been observed by a neurologist with suspected multiple sclerosis, demyelinating optic neuritis, and therefore received treatment, including corticosteroid therapy, which did not give a positive result. The patient underwent a standard ophthalmological examination, optical coherence tomography (OCT) of the retina and optic nerve, and computer perimetry. The additional survey data were non-specific in nature. Taking into account the patient’s complaints, anamnesis of the disease, the data of the research methods, as well as the potential possibility of combining LHON with neurological symptoms, three years later the hereditary nature of the disease was suspected. Using MLPA (Multiplex Ligation-dependent Probe Amplification) and direct automatic sequencing, the patient was tested for frequent LHON mutations. Mutation m.11778 G>A was detected. In clinical practice, it is necessary to keep in mind the existence of patients with LHON in combination with neurological symptoms, both of them can manifest before and after vision acuity decline which could lead to misdiagnosis and, as a result, incorrectly prescribed treatment. The combination of symptoms of vision loss with the characteristic features of hereditary optical neuropathy in combination with neurological symptoms should encourage clinicians to prescribe a genetic analysis of patients for LHON mutations.